Validity and reliability of the executive function scale in Cuban university student - Díaz-Guerra, Diego D.; Hernández-Lugo, Marena De La C.; Ramos-Galarza, Carlos; Broche-Pérez, Yunier (Frontiers in Psychology, 2025)
IntroductionExecutive functions are higher cognitive skills involved in planning, organization, decision-making, impulse control, and working memory. It is essential to have tools that allow for the accurate and reliable assessment of this construct in university students. This study aims to evaluate the validity and reliability of the Executive Functions Scale for University Students (UEF-1) in the Cuban population.MethodsA cross-sectional study was conducted in which an online survey was administered to 1,092 Cuban university students representing 14 of the country’s 16 provinces. Descriptive analyses, confirmatory factor analyses, and Pearson correlation analyses were used to assess the psychometric properties of the scale.ResultsSignificant correlations were obtained between the scale factors, and the original seven-factor structure was confirmed. The scale demonstrated good internal consistency and overall reliability (α = 0.91, ω = 0.91).ConclusionThe study provided evidence that the UEF-1 is a reliable and valid tool for assessing executive functions in Cuban university students. This measure provides a comprehensive understanding of the cognitive abilities and functioning of Cuban university students, allowing for the identification of specific areas of executive functioning that may benefit from additional support or intervention.